Application Of Electronic Justice To Improve Quality Judicial Services At The South Jakarta Religious Court - Syamsurizal Syamsurizal; Agung Edi Rustanto; Teguh Sandjaya (Universitas Padjadjaran, 2023)
The focus of this research is the implementation of electronic justice at the South Jakarta Religious Court. The method used in this research is descriptive qualitative by adopting the Grindle model. The level of success is determined by the level of policy feasibility. Primary data was obtained by interviews, observation and data analysis using a spiral model. Research results on policy content components: In the interest affected aspect, the implementation of electronic justice without being motivated by the interests of certain groups. In the Type of Benefits aspect, the benefits are felt by the parties concerned. In the Extent of Change Envision aspect, case settlement costs are lower, the case process is faster, the trial process is easy to carry out. In the Site of Decision Making aspect, the Supreme Court decision is made by the chairman of the Religious Court. In the program implementer aspect, the program implementers are religious court officers, advocates, and people who have cases. In the Committed Resources aspect, the supporting resources are sufficient. In the context of Implementation component: In the aspect of power, interest, and strategy of actors involved, the implementing actors are the Supreme Court, Religious Courts, Advocates and the community as users. In the Institution and Regime Characteristic aspect, where the Chair of the Religious Court decides to implement electronic justice, In the aspect of Compliance and Responsiveness, the South Jakarta Religious Court and advocates comply with electronic justice.